Targeting Gut Microbiota With Natural Polysaccharides: Effective Interventions Against High-Fat Diet-Induced Metabolic Diseases - Sun, Chao-Yue; Zheng, Zuo-Liang; Chen, Cun-Wu; Lu, Bao-Wei; Liu, Dong (Frontiers in Microbiology, 2022)
Unhealthy diet, in particular high-fat diet (HFD) intake, can cause the development of several metabolic disorders, including obesity, hyperlipidemia, type 2 diabetes mellitus (T2DM), non-alcoholic fatty liver disease (NAFLD), and metabolic syndrome (MetS). These popular metabolic diseases reduce the quality of life, and induce premature death worldwide. Evidence is accumulating that the gut microbiota is inextricably associated with HFD-induced metabolic disorders, and dietary intervention of gut microbiota is an effective therapeutic strategy for these metabolic dysfunctions. Polysaccharides are polymeric carbohydrate macromolecules and sources of fermentable dietary fiber that exhibit biological activities in the prevention and treatment of HFD-induced metabolic diseases. Of note, natural polysaccharides are among the most potent modulators of the gut microbiota composition. However, the prebiotics-like effects of polysaccharides in treating HFD-induced metabolic diseases remain elusive. In this review, we introduce the critical role of gut microbiota human health and HFD-induced metabolic disorders. Importantly, we review current knowledge about the role of natural polysaccharides in improving HFD-induced metabolic diseases by regulating gut microbiota.